Relationship between Sodium Intake and Nutritional Knowledge with the Incidence of Hypertension in Inpatients of Harapan Indah Sendawar Hospital - Juni Mariati Simarmata; Mudhrikah Mudhrikah; Deddy Sepadha Putra Sagala; Elfrida Simanjuntak; Debi Dinha Octora (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Hypertension is a major public health problem with a prevalence that continues to increase both globally and nationally. This condition is often referred to as a “silent killer” because it usually presents without symptoms yet may lead to severe complications such as heart disease, stroke, and kidney failure. Data from the 2018 Basic Health Research (Riskesdas) revealed that the prevalence of hypertension in Indonesia reached 34.1% among individuals aged ≥18 years, showing an increase compared to 2013. One contributing risk factor is excessive sodium intake that exceeds daily recommendations, combined with poor nutritional knowledge influencing individual dietary behaviors. This study employed an observational analytic design with a cross-sectional approach to analyze the association between sodium intake and nutritional knowledge with the incidence of hypertension among inpatients at Harapan Insan Sendawar General Hospital. The study population included all elderly patients aged over 60 years (n = 36), selected through total sampling. Primary data were collected via interviews using a semi-FFQ questionnaire and blood pressure measurements, while secondary data were obtained from hospital records. Findings showed that most respondents were over 60 years old (61.1%), had high sodium intake (80.5%), and low nutritional knowledge (72.2%). The prevalence of hypertension among respondents was remarkably high at 94.4%. Statistical analysis demonstrated a significant association between sodium intake and hypertension (p = 0.010), as well as between nutritional knowledge and hypertension (p = 0.032). In conclusion, high sodium consumption and low nutritional knowledge significantly contribute to the incidence of hypertension among elderly patients. These findings highlight the importance of nutrition education and sodium intake control as preventive strategies for hypertension.